1977
DOI: 10.1111/j.1432-1033.1977.tb11639.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Role and Mode of Operation of the Very‐Lysine‐Rich Histone H1 in Eukaryote Chromatin

Abstract: Limited digestion with trypsin of both calf thymus H1 histone and the fragment 1 -120 of the H1 molecule has resulted in the isolation of the fragment 35-120. This fragment assumes a globular structure under physiological conditions of pH and ionic strength. The variable N-terminal portion of the molecule, up to residue 34, is not required for the formation of the HI globular structure.Proton nuclear magnetic resonance (NMR) and ultracentrifugation studies show that the H1 histone molecule consists of three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0
5

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(127 citation statements)
references
References 18 publications
7
115
0
5
Order By: Relevance
“…This is supported by physical studies of Hi in solution [9]. The three domains are: the amino terminal segment (residues which is largely unstructured; the central structured region (residues which may -be folded into a specific tertiary structure [9,10], the highly basic carboxyl ter-minal half which appears to be in a random conformation. These three structural domains may be associated with three quite distinct functional roles in the various orders of folding of the basic nucleosome fibre.…”
Section: Introductionmentioning
confidence: 87%
“…This is supported by physical studies of Hi in solution [9]. The three domains are: the amino terminal segment (residues which is largely unstructured; the central structured region (residues which may -be folded into a specific tertiary structure [9,10], the highly basic carboxyl ter-minal half which appears to be in a random conformation. These three structural domains may be associated with three quite distinct functional roles in the various orders of folding of the basic nucleosome fibre.…”
Section: Introductionmentioning
confidence: 87%
“…Earlier studies [6,7] of the structure of the peptides excised from histones H1 and H5 by trypsin digestion showed that they contained all the secondary and tertiary structure found in the intact parent molecule. The same finding is reported here for sea urchin sperm histone 41.…”
Section: The Conformation Of the Peptide G$lmentioning
confidence: 99%
“…It has previously been demonstrated that both calf thymus histone H1 [6] and chicken erythrocyte H5 [7] consist of three structural domains in free solu- tion. Histone 41, although clearly an HI histone, shows very considerable compositional and sequence differences from calf thymus H1 and from chicken erythrocyte H5 [lo, 15,201.…”
Section: Conclusion and Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the specificity is different from one kinase to another, the sites of phosphorylation in histone H5 are distributed in vitro as in vivo in two distinct regions of the protein: the amino-terminal region (residues 1-21) and the carboxy-terminal region (residues 101-189); in all cases, no site has been detected in the globular part of the molecule (residues 22-100) [9]. This fact has been already mentioned for histone H 1 which, like histone H5, conrains 3 different domains: a short apolar amino-terrninal part in random coil (residues 1-34); a globular central part (residues 35-120); and a highly basic carboxy-terminal part in random coil (residues 121-213) [10]. Phosphorylation of histone H1 by a cyclic AMPdependent protein kinase only takes place at serine residue 37 in the amino-terminal region of the molecule while phosphorylation by a cyclic AMP-independent protein kinase occurs at serine and threonine residues, mainly in the carboxy-terminal region.…”
Section: Introductionmentioning
confidence: 68%